Effect of Ciprofloxacin on Recovery and Conception Rate in infectious Repeat Breeder Crossbred Cows - Bhardwaj, Anavil; Nema, SP; K, Sudarshan; Madhwan, Ritika; Shrivastav, Nidhi; Shukla, Supriya (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was undertaken to evaluate the therapeutic efficacy of Ciprofloxacinin in 20 infectious repeat breeder crossbred cows brought to the AI centre of Department of Veterinary Gynaecology and Obstetrics, College of Veterinary Science and Animal Husbandry, Mhow and nearby Government AI centers. Animals were divided into two groups ten in each .The animals in first group were treated with Ciprofloxacin Hydrochloride @ 4 mg/kg BW IU. The animals in control group were infused with 30 ml saline IU. Bacterial count, total Cellular count and PMNs values were reduced highly significantly (P < 0.01) in Ciprofloxacin treated group than in control group. 90.00 % cows under Ciprofloxacin treatment became negative to White side test. An overall conception rate of 70.00 per cent was found in Ciprofloxacin treated repeat breeder cross bred cows. most common method of treatment is both Repeat breeding alone is a major cause of infertility and economic loss to dairy farming. Reproductive tract infections, has been attributed to be one of the most important factors. The incidence of repeat breeding had been reported to vary from 7.31 to 23.88 per cent among bovines (Singh, 1991). Prasad (2006) recorded higher bacterial load prior to treatment per ml of cervical mucus in cases of endometritis. The intrauterine (Galvao et al., 2009 and Galvao, 2011) or systemic (Chenault et al., 2004) antibiotic administration. The present study was carried out to evaluate the efficacy of ciprofloxacin I/U infusion in repeat breeder cross bred cows.
Keywords: Repeat breeders; uterine flushing; Ciprofloxacin; PMNs; Conception Rate.